PENERAPAN METODE ROLE PLAYING UNTUKMENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PAI DAN BUDI PEKERTI SDN 002 LOGAS KECAMATAN LOGAS TANAH DARAT - Ratih Gumala Dewi; Zulhaini Zulhaini; A Mualif (Universitas Islam Kuantan Singingi, 2022)
The study aims to find out how the learning outcomes of students before the application of the Role Playing method at SDN 002 Logas, how the learning outcomes of studentsvafter the aplicationof the role playing method at SDN 002 Logas,This study uses CAR(Classroom Action Research) where the total number of student at SDN 002 Logas Population is 153 student and thesampe class V SDN 002 Logas Specifically. This research is 12 people, considting of 3 boys and 9 girls. While the technique used is interview document study,ovsevation,documentation test.,Showed the following symptoms or phenomena. Of the 12 students when the daily tests was heldonly 5 people (46.66%) who scored above the established KKM, which is 75, while others (53.34%) value is still incomplete. When given test questions, only 60% of all students can answer the questions correctly. Each time given a homework assignment, the average student grade still gets low marks, this is seen when examined together only 53.34% of the majority of students can answer the assignment correctly. Although it has been taught about the subject of morals, but student behavior has not shown significant change. When remedial was held for the second time it turned out that there were still scores of students under the KKM 75. This study aimed to find out the application of the Role Playing metod to improve learning outcomes in Islamic religious education subjects and Budi Pekerti material Getting to Know the Apostles of Allah class students V State Elementary School 002 LogasLogas Tanah Darat District. Based on the results of data collection by means of observation, interviews and documentation, then the data were analyzed descriptively-qualitative through diagrams or graphs and it can be concluded that the Application of Design A Test Strategy can improve the learning outcomes of Grade V students in Islamic Religious Education and Culture Allah's Apostles in State Elementary School 002 Logas, District of Logas Tanah Darat, this is proven by an increase in student learning outcomes ranging from pre-Cycle to Cycle III with a percentage of 73.91 (pre-cycle), 75.66 (Cycle I), 78, 41 (Cycle II) and 84.41 (Cycle III). So student learning outcomes V at SD2 002 Logas continue to increase according to the results of the evaluation of the percentage increase from cycle I to Cycle II is 2.75% and from Cycle II to Cycle III is 6%.